PENERAPAN MODEL PROJECT BASED LEARNING (PjBL) DALAM PEMBELAJARAN MENULIS TEKS IKLAN SERTA IMPLIKASINYA TERHADAP SELF-CONFIDENCE SISWA KELAS V SEKOLAH DASAR DI KECAMATAN CIMALAKA - Sri Nurbaeti; Sulyati, E; Aminah, Mimih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low ability of students to write advertising texts and their lack of self-confidence during the learning process. One approach to addressing these issues is the implementation of the Project-Based Learning (PjBL) model, which enables students to learn actively through meaningful project activities. This study aimed to determine the impact of the PjBL model on the advertising text writing skills and self-confidence of fifth-grade elementary school students in Cimalaka District. A quantitative approach was employed using a quasi-experimental method with a non-equivalent control group design. The research subjects comprised two classes: an experimental class taught using the PjBL model and a control class taught using conventional methods. Data were collected through advertising text writing tests and self-confidence questionnaires. Data analysis involved normality testing, the Mann-Whitney U test, and hypothesis testing. The results indicated no significant difference in initial ability between the experimental and control classes; this was confirmed by the Mann-Whitney test on pretest scores, which yielded a significance value of 0.694 (p > 0.05). Following the intervention, a significant difference was observed between the posttest results of the experimental and control classes, with a significance value of 0.000 (p < 0.05). These findings demonstrate that the PjBL model is effective in influencing the advertising text writing skills of fifth-grade elementary students. Furthermore, the implementation of the PjBL model had a positive impact on student self-confidence, evidenced by increased willingness to express opinions, collaborate in groups, and present completed projects.